Pre-Disasters Management Analysis of Mount Sinabung Eruption in Kutagugung Village, Namen Taren District, Karo Regency, North Sumatera - Susilawati; Aisyah Sholeh Al-Anshary; Atikah Pratiwi; Eva Mulyani S; Kurnia Permata Sari; Nadia Safira Siregar; Salwa Radha Hera (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to analyze pre-disaster management of the Mount Sinabung eruption in Kutagugung Village, Naman Teran District, Karo Regency. The focus of the research includes government and community preparedness, the effectiveness of early warning systems, and mitigation programs in raising community awareness of disaster risks. The study uses a qualitative method with a case study approach. Data were collected through in-depth interviews, field observations, and documentation. The results show that community awareness of Mount Sinabung's status as an active volcano varies, with most understanding the risks but requiring further education. Disaster management organizations, such as BNPB and Karang Taruna, have been active, although broader community involvement needs improvement. Disaster mitigation training is considered effective in enhancing preparedness, but its scope remains limited to specific groups. The local tradition Erpangir Ku Lau holds significant potential for integration into mitigation strategies, although it has not yet been optimally utilized. Disaster management infrastructure, such as evacuation routes, assembly points, and shelters, is available but requires quality improvements and sustainable maintenance. Existing early warning systems are helpful but need modernization and expanded coverage. This study concludes that collaboration between the government, the community, and the utilization of local wisdom is key to enhancing the resilience of Kutagugung Village in facing the risks of the Mount Sinabung eruption.